Pengembangan Kapasitas Aparatur Sipil Negara di Daerah - Arif Mulyono (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2015)
The purposes of this study was to analyze and describe the transparency of the capacity building of state apparatus and harmonization of development policy on the state apparatus in the area. This type of research used qualitative descriptive approach. Data collected through literature study that is derived from primary data and secondary data. Based on the analysis related to manage and develop the capacity of civil state apparatus in the area indicate that Computer Assisted Test (CAT) method for recruitment of civil servant in Sidoarjo is one form of a positive transparency that is expected to create a cadre of civilian apparatus qualified and competent. The use of this method aimed to develop the quality of personnel resources. In addition, it is supported by policy on the capacity building of civil state apparatus which is comes from center. But, in reality its policy is not harmonized. It is indicated by policy on learning permits and learning task as a form of capacity building of civil state apparatur is irrelevant between the center and the local. So that implementer actors have difficulty in its implementation.